2016
DOI: 10.3892/mco.2016.767
|View full text |Cite
|
Sign up to set email alerts
|

A prospective feasibility study to evaluate neoadjuvant-synchronous S-1 with radiotherapy for locally advanced rectal cancer: A multicentre phase II trial

Abstract: Treatment results of locally advanced rectal cancer without preoperative chemoradiotherapy (CRT) in Japan do not differ from those of Western countries. Preoperative CRT with new anticancer agents may decrease local recurrence rate and prevent distant metastases, thus improving survival. We conducted a trial to evaluate feasibility of neoadjuvant CRT using S-1 in patients with locally advanced rectal cancer. A multi-institutional (17 specialized centres), interventional, phase II trial was conducted from April… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
16
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 39 publications
7
16
1
Order By: Relevance
“…Sato et al reported good outcomes, with increased rates of completing treatment (86.6%) and pathological complete response (pCR; 34.7%), in a phase II trial of neoadjuvant preoperative CRT with S-1 plus irinotecan and radiation in patients with locally advanced rectal cancer 9) . We also conducted a phase II trial to evaluate neoadjuvant-synchronous S-1 with radiotherapy for locally advanced rectal cancer and demonstrated its short-term safety 10) . There are only a few reports on the short-term outcomes of neoadjuvant CRT using S-1 for locally advanced rectal cancer, and long-term outcomes for patients receiving this regimen remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Sato et al reported good outcomes, with increased rates of completing treatment (86.6%) and pathological complete response (pCR; 34.7%), in a phase II trial of neoadjuvant preoperative CRT with S-1 plus irinotecan and radiation in patients with locally advanced rectal cancer 9) . We also conducted a phase II trial to evaluate neoadjuvant-synchronous S-1 with radiotherapy for locally advanced rectal cancer and demonstrated its short-term safety 10) . There are only a few reports on the short-term outcomes of neoadjuvant CRT using S-1 for locally advanced rectal cancer, and long-term outcomes for patients receiving this regimen remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…From April, 2009 to August, 2011, a total of 37 patients diagnosed with primary rectal cancer were prospectively enrolled in a multicenter phase II study (UMIN ID 03396). The trial design and eligibility criteria have been previously reported (12). Of the 37 patients, 26 whose biopsy specimens were available for microarray analysis were investigated in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…The details of the CRT were previously described (12). CRT was administered concurrently with four cycles of chemotherapy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oral fluoropyrimidine S-1, an anti-cancer drug invented in Japan, is designed to improve 5-FU's antitumor activity while reducing gastrointestinal toxicity 22) . Gimeracil, a dehydropyrimidine dehydrogenase (DPD) inhibitor, is reported to have a radio sensitizing property when combined with S-1 23) , and there have been several reports of CRT using S-1 for rectal cancer mainly from Japan [24][25][26] .…”
Section: Introductionmentioning
confidence: 99%